Strategi Penyelesaian Eksekusi Terhadap Benda Jaminan dalam Pembiayaan Murabahah pada Perbankan Syariah - Supriyadi Supriyadi (ITB AAS INDONESIA Surakarta, 2020)
The urgency of collateral in financing is important for the sustainability of Islamic banking in order to contribute to the economy of the people. But often if the debtor wan achievements, creditors have difficulty in executing collateral objects, therefore it is necessary to have a strategy to settle collateral objects in Islamic financing. This research is a doctoral study using secondary data which includes primary legal materials, secondary legal materials and tertiary legal materials and analyzed with a qualitative approach. Strategy for settlement of collateral objects in sharia financing must be seen from the position of collateral objects that are assesoir from the principal contract, namely debt or financing. To prevent fears from banks that debtors do not pay off their financing or default, objects are needed as collateral. Completion of the execution of objects which are the object of collateral in financing can be through three strategies, namely selling collateral objects under the hand, conducting public auctions and through justice. In principle, if the debtor wan achievements, the objects can be executed to pay off debtor obligations.